SERUM LEVEL MEASUREMENTS OF Gc, Cp, IgG, IgA, AND 1gM IN PATIENTS WITH FAVISM, IN IRAN - D.D.Farhud ; H.Sadighi ; P.Amirshahi ; F. Sh. Tavakkoli (Tehran University of Medical Sciences, 1993)
The quantitative measurements of Gc(P37, C=20); ('p(P=4O, C=20); lgG(P=67. C= 50);IgA(P- 67,C: :50)and 1gM (P=67,('=50) were carried out on patients with Favism and healthy individuals, both school boys, from the Caspian sea litlorals. Comparison of' these groups revealed differences, significant for Gc (X2 =10.177), lgM(X2 9.6151), lgA(X2 9.2821), highly significant for IgG (X2=47.1228), and not significant for Cp(X2= 1.4762). The observed increase in the controls could be due to the environmental effects, e.g, the presence of different diseases which needs adaptation to high levels of' serum proteins and the immunoglobulins. The normal range maintained in the patients is suggested to be due to positive selection inducing a developed immune response and producing better chances not to get affected by some other endemic infectious diseases such as malaria (P.falciparum).